CASE STUDY OF ACUTE PAIN WITH ANTERIOR COMMUNICATING ANEURYSM IN ELDERLY PATIENTS IN THAILAND - Septian Galuh Winata; Chlara Yunita Prabawati; Mariyatul Kiptiyah; Diah Priyantini (Universitas Airlangga, 2026)
Introduction: Acute pain in older adults requires comprehensive assessment because it may affect physical function, emotional comfort, and recovery, particularly after neurological conditions such as anterior communicating artery aneurysm. This case study aimed to analyze pain assessment, nursing diagnosis, and non-pharmacological nursing interventions in an elderly patient with acute pain after anterior communicating artery aneurysm surgery. Methods: A descriptive case study was conducted at Srinagarind Hospital, Khon Kaen University, Thailand. One elderly postoperative patient was selected using purposive sampling based on the presence of acute pain following anterior communicating artery aneurysm surgery. Pain was assessed using the PQRST assessment, Numeric Rating Scale (NRS), DOLOPLUS, and Short-Form McGill Pain Questionnaire (SF-MPQ). Non-pharmacological pain management was provided through relaxation and guided imagery as complementary nursing interventions. Results: The PQRST assessment showed that the pain was related to the aneurysm condition and was described as pressure and throbbing pain in the frontal head area, occurring after waking and during continuous activity. The NRS score was 8/10 on the first postoperative day, indicating severe pain, and decreased to 5/10 after non-pharmacological intervention, indicating moderate pain. The DOLOPLUS score was 14, suggesting significant pain with potential interference in daily activities and comfort. The SF-MPQ score was 12, indicating moderate pain involving both sensory and affective dimensions. Based on these findings, the nursing diagnosis was acute pain related to physiological injury agents. Conclusions: Comprehensive pain assessment using multiple instruments helped nurses identify the intensity, characteristics, behavioral expression, and sensory-affective aspects of pain in an elderly postoperative patient.